171P Treatment (tx) patterns of patients with advanced renal cell carcinoma (aRCC) receiving first-line (1L) tx: Results from a cross-sectional real-world study. (15th December 2019) - Zanotti, G; Kim, R; Krulewicz, S P; Hall, J P; Leith, A; Bailey, A; Liu, F; Kearney, M
Abstract: Background: Personalised tx is key in aRCC. The International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) model determines prognosis of aRCC patients treated with systemic tx, helping guide treatment choice. This study examined real-world tx patterns and outcomes of 1L aRCC patients with differing IMDC status in the US. Methods: Real-world data were drawn from the RCC Disease Specific Programme TM ; a cross-sectional study administered to oncologists, nephrologists and urologists in the US. Physicians completed patient record forms (PRFs) for up to the next 8 consulting RCC patients receiving active drug tx, from February - September 2019, plus additional optional PRFs for patients receiving/who had received either 1L nivolumab/ipilimumab combination tx or cabozantinib tx, where these patients were available. Study variables included patient demographics, background clinical information and tx patterns. Results: Physicians (n = 82) provided data on 687 patients. 445 patients were receiving 1L tx at time of data abstraction. Of those receiving 1L tx, mean age was 64.2 years, and 69% of patients were male. 34% (n = 151) did not have a physician-assessed IMDC prognostic risk score, and 5% (n = 23) reported unknown. Of the 61% (n = 271) that had a physician-assessed IMDC prognostic risk score, 15% had a low risk, 63% had an intermediate risk and 21% had a high risk. In the intermediate and high risk group, tyrosine kinase inhibitor (TKI) monotherapy was the most common 1L therapy (45%, n = 103), followed by IO-IO combination (29%, n = 66). Conclusion: ASCO and NCCN guidelines recommend IO-IO combination in patients with an intermediate or high IMDC risk. However, at the time of data collection, more patients meeting these criteria received TKI monotherapy than IO-IO combination; moreover, almost a third of 1L tx aRCC patients were not even assessed. Newly introduced IO-TKI combination tx, approved during the fieldwork period, could enable clinicians to offer patients personalised tx, irrespective of risk profile. Legal entity responsible for the study: Pfizer Inc. Funding: Pfizer Inc. (part of an alliance between Pfizer Inc. and Merck KGaA, Darmstadt, Germany). Disclosure: G. Zanotti: Shareholder / Stockholder / Stock options: Pfizer; Full / Part-time employment: Pfizer. R. Kim: Full / Part-time employment: Pfizer; Shareholder / Stockholder / Stock options: Exelixis. S.P. Krulewicz: Shareholder / Stockholder / Stock options: Pfizer; Full / Part-time employment: Pfizer. J.P. Hall: Full / Part-time employment: Adelphi Real World. A. Leith: Full / Part-time employment: Adelphi Real World. A. Bailey: Full / Part-time employment: Adelphi Real World. F. Liu: Full / Part-time employment: EMD Serono, Inc. M. Kearney: Full / Part-time employment: Merck KGaA, Darmstadt, Germany; Shareholder / Stockholder / Stock options: Novartis Pharma; Shareholder / Stockholder / Stock options: UCB Pharma; Shareholder / Stockholder / Stock options: SPRL.